Regression and forecasting study on water quality in Malaysia: article - Safingi, Saufi; Mohd Safaai, Nor Sharliza (2017)
Water pollution is a serious problem in Malaysia and affect negatively on the sustainability of water resources. In addition, it also causing negative impacts on plants and organism living, people’s health and the country’s economy. The tremendous quantity of water resources available in the catchment unfortunately does not guarantee enough supply to all users because of the river pollution. To overcome this problem, water pollution control plant was chosen as advanced wastewater treatment facility serving residents, businesses and industries. In this study, Regression analysis such as linear regression or non-linear regression are used to predict the value of parameter of water quality which is based in BOD, TSS and ammoniacal nitrogen (AN) and perform curve fitting for water quality in Malaysia by using least square regression. the regression analysis was run in the excel by using collected data form Environmental Quality Report 2014 to identify the best model that represent the pattern of the water quality. Linear and non-linear regression were performed by using Analysis Toolpak in the excel add-ins. Results shows that the BOD in water is increasing across the year. By using the regression equation, it was forecasted that the number of river which is polluted by BOD is about 879 at the year of 2020. BOD level can be reduced if water pollution treatment plant was applied to residents, businesses and industries.